Anti-inflammatory effects of androgens in the human vagina. (October 2020) - Maseroli, Elisa; Cellai, Ilaria; Filippi, Sandra; Comeglio, Paolo; Cipriani, Sarah; Rastrelli, Giulia; Rosi, Martina; Sorbi, Flavia; Fambrini, Massimiliano; Petraglia, Felice; Amoriello, Roberta; Ballerini, Clara; et al.
Abstract : Chronic inflammation is involved in the genitourinary syndrome of menopause (GSM) and beneficial effects of androgens in the vagina have been described. We investigated the potential involvement of human vagina smooth muscle cells (hvSMCs) in the inflammatory response and the immunomodulatory effect of androgen receptor (AR) agonist dihydrotestosterone (DHT). HvSMCs isolated from menopausal women were evaluated for sex steroids receptors and toll-like receptors mRNA expression, and left untreated or treated in vitro with lipopolysaccharide (LPS) or IFNγ, in the presence or absence of DHT. We evaluated mRNA expression (by RT-PCR) and secretion in cell culture supernatants (by a bead-based immunoassay) of pro-inflammatory markers. Nuclear translocation of NF-κB (by immunofluorescence) and cell surface HLA-DR expression (by flow cytometry) were also evaluated. Similar experiments were repeated in rat vSMCs (rvSMCs). In hvSMCs and rvSMCs, AR was highly expressed. DHT pre-treatment inhibited LPS-induced mRNA expression of several pro-inflammatory mediators (i.e. COX2, IL-6, IL-12A and IFNγ ), effect significantly blunted by AR antagonist bicalutamide. DHT significantly counteracted the secretion of IL-1RA, IL-2, IL-5, IL-15, FGF, VEGF and TNFα. LPS-induced NF-κB nuclear translocation was significantly inhibited by DHT, an effect counteracted by bicalutamide. DHT pre-treatment significantly decreased IFNγ-induced expression of HLA-DR, mRNA expression of iNOS, COX2 and MCP1, and secretion of IL-1, IL-2, IL-5, IL-6, MCP1 and GCSF. Similar effects were observed in rvSMCs. The activation of AR suppresses the inflammatory response in hvSMCs, reducing their potential to be involved in the initiation and maintaining of inflammation, thus representing a therapeutic strategy in conditions, such as the GSM.